Multilateralism in Agony and Its Challenges for the Future - González, Dayanara (2025)
Talking about multilateralism as part of a globalized world is common, especially in International Relations; however, the use of this concept is usually in its literal sense, without understanding its qualitative aspect, importance and the evolution it has had over the years. Therefore, this essay will use the theoretical contribution of John Gerard Ruggie in his article Multilateralism: the Anatomy of an Institution, with the aim of having a more complete definition, identifying its characteristics and the role that the United States had in shaping it after the postwar, but also clarifying that its existence preceded it. On the other hand, it will be determined the main challenges that have been presented to the multilateral, including the leading role that China has acquired and the competition between actors, as well as showing that it is not new that multilateralism is in crisis, but that this has been worsened with the COVID-19 pandemic. In fact, this has shown how nationalism and individualistic policies in the vaccine production and vaccination process have prevailed over the calls of institutions such as the World Health Organization for global solidarity and international cooperation.